AMBIVALENSI PERILAKU MAHASISWA SANTRI DALAM ERA GLOBALISASI - Suhermanto Suhermanto (Nurul Jadid University, 2017)
College Student, is a community of intellectual candidates who will become leaders in the future, the successor of leadership in his era later. Therefore it is fitting to get all of us attention with guidance, direction, and others including by introducing them to the real world that full of challenges, not to mention the students who are in the sub-culture of the pesantren. Although pesantren itself was initially only an entity to deepen the sciences of Islamic science, but in further development, due to its flexibility, and the demands of the people's need for